A progressividade dos tributos diretos nas Pesquisas de Orçamentos Familiares (POFs) 2008-2009 e 2017-2018 - Pedro Humberto Bruno de Carvalho Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This study analyzes the distribution of frequency and income share of four direct taxes among Brazilian households - property tax, vehicle tax, personal income tax on labor income, and social contributions - per income and geographical strata, based on the last two Household Budget Surveys of 2008-2009 and 2017-2018. The study found that property tax and labor income tax are progressive up to the 1% richest, which starts to decrease their ratio on household income. Vehicle tax and social contributions are regressive, mainly due to the recent increase of vehicles ownership among the poorer and the ceiling of the general social contributions among income above six minimum wages, respectively. Finally, this study makes some proposes to the tax reform to enhance progressivity.
Keywords: H33; 330; direct taxes; property tax; vehicle tax; personal income tax; social contribution; household budget survey; tax progressivity